Financial Institutions Readiness Towards Cryptocurrency Adoption: A Case of Banks in Tanzania - pastory dickson; Desderius A. Mahwera (Profesional Muda Cendekia Publishing, 2022)
This study assessed readiness of Tanzania’s financial institutions towards adoption of cryptocurrency. Specific objectives included assessing the attitudes of bank staff on cryptocurrency, determining current readiness level of Tanzania’s banks towards adoption of cryptocurrency and examining the relationship between staff attitude and adoption readiness. The study used a mixed-method research design. Purposive and simple random sampling strategies were deployed for selecting 195 participants from both public and private banks located in Dar es Salaam. Data were collected by using structured questionnaires and semi-structured interviews and analyzed through descriptive statistics and content analysis techniques. Findings of the study revealed that staff had negative and positive attitude on perceived usefulness and perceived ease of use of cryptocurrency, respectively. Moreover, overall cryptocurrency adoption readiness was found at low level and, a weak positive significant correlation was found between attitude and adoption readiness. It was concluded in this study that a bank sector is not ready to adopt cryptocurrency. From the findings it was recommended among others that Tanzania’s banks should start to provide trainings on cryptocurrency to staff and, policy and regulations should be formulated to support cryptocurrency usage in the country.